Betting on you : how to put yourself first and (finally) take control of your career - Ruettimann, Laurie (New York : Henry Holt and Company, 2021)
"A revolutionary guide for improving your workplace experience, with hilariously relatable anecdotes and tips for professional growth, from popular podcast host and veteran human resources specialist Laurie Ruettimann"--
Includes index.
HB
Keywords: Career development; Success -- Psychological aspects